The last brother : a Civil War tale - Noble, Trinka Hakes (Tales of young Americans series., 2006)
Eleven-year-old Gabe enlists in the Union Army in Pennsylvania along with his older brother Davy and, as bugler, does his best to protect Davy during the Battle of Gettysburg.